(untitled) (Asian Journal of Pharmaceutics (AJP), 2023)
Objective: Acyclovir (ACV), a highly specific inhibitor of herpes virus replication, is applied topically into the eye to treat ocular keratitis. The main aim of this study was to formulate and characterize eye drops containing ACV microspheres against herpes simplex-induced keratitis. The microspheres are small spherical particles with diameters ranging from 10 to 1000 μm. It increases bioavailability while decreasing side effects. Materials and Methods: The solvent evaporation technique was used to develop the microspheres for the sustained release drug delivery system. Crystalline methylcellulose, sodium alginate, calcium chloride, and chitosan were the polymers used. The drug content, encapsulation efficiency, in vitro drug release studies, stability studies, viscosity, pH measurement, and clarity test were all performed on the microspheres. Results: Particle size and shape, percent entrapment, in vitro drug release, compatibility studies, and other characteristics of microsomes were assessed. These drug delivery systems demonstrated good increased solubility and sustained release, which is necessary for bioavailability and therapeutic action, due to their matrix nature. The formulation has an acceptable shape and particle size, no chemical interactions, and is stable under refrigeration, according to the results of the characterization parameters and stability research. Conclusion: Eye drops containing microspheres of ACV could be considered a promising sustained drug delivery system for ocular keratitis treatment.